The investigative competences. A demand of the XXI Century - López Osorio, Jorge Hernán
This research was carried out with the purpose of investigating how to strengthen investigative skills in apprentices, and to know what methodological strategies and active didactic techniques are used by instructors to encourage critical and reflective thinking in the learning environment. The results were obtained through a diagnosis compiled through the application of surveys, questionnaires and the method of observation; highlights the findings, participation, cooperation and commitment of instructors and apprentices of the Technologist in Market Management program, SENA Trade and Services Center, Atlantic Regional.